Predictors of Talent Retention among Academicians in Private Colleges and Universities in Yunnan Province - Zheng Xinhua; Anbalagan Marimuthu (International Journal of Education and Humanities, 2024)
In the past few decades, private colleges and universities have made great progress in China and become indispensable to China's higher education system. In recent years, China's private colleges and universities have made great progress, in terms of development scale and school quantity has played a positive role in cultivating outstanding students and promoting social development. The construction of these private colleges and universities fills the gap in educational resources and provides more learning opportunities to meet the needs of students at different levels and majors. Although private colleges and universities in China have made significant achievements, they face some problems and challenges. This includes an increase in the education scale and a low quality of education. According to statistics from the Ministry of Education, compared with public universities, private colleges and universities face certain difficulties in attracting and retaining excellent academicians. So this study will combine the background of the times and the status quo of talent retention in private colleges and universities to predict the factors affecting the retention of academician talents in private colleges and universities in Yunnan Province, adopt quantitative research methods, obtain data through questionnaire surveys, and then analyze it to provide guidance for the system construction, healthy development, and smooth development of private colleges and universities, suggesting ideas to improve talent retention rates and promote the teaching quality of private colleges and universities